How can the buffalo carcass be used rationally? - Ricardo Alexandre Silva Pessoa (Revista Científica)
The objective of this study was evalue the yields of meat cuts and discards obtained from the carcass of buffalo steers. The research was carried out in the Bubalinoculture Sector of the Animal Science Department of the Federal Rural University of Pernambuco, Brazil. 62 carcasses of pasture-finished cross- bred buffalo steers were evaluated. The animals weighed an average of 507.0 kg and were slaughtered before the first molt of the deciduous dentition, with a carcass yield of 49.0%. The carcass of each animal was divided into two half-carcasses, which were identified and weighed. The carcasses were taken to a cold chamber at 4 ºC during 24h. To obtain the yield of each integral primary cut, the carcasses were sectioned into front and rear, which were weighed and boned. Boning was car- ried out by the same employees to maintain the standard cuts and dressing. The cuts with and without bones, the edible flap (meat and fat shavings), the discarded flap (tallow, nerves and skins) and the discarded bones were obtained. The deboning standard used was typical of the Brazilian market with dressing between moderate and severe. The percentages observed for the cuts (in each half carcass) were: soft drumstick, 5.3%; hard cushion, 3.7%; duckling, 3.8%; lizard, 1.8%; sirloin steak, 1.1%; grill flank steak, 0.75%; red flank steak, 0.61%; breast, 0.96%; rump baby beef, 1.3%; rump bonbon, 0.8%; ossobuco, 4.2%; muscle, 2.0%; turkey bone, 1.1%; duckling bone, 0.5%; oxtail, 0.38%; ancho steak, 1.3%; chorizo steak, 1.9%; filet mignon, 1.2%; fillet shell, 0.35%; chest, 3.9%; neck, 4.2%; acm, 4.3%; window rib, 8.7%; strip roast, 2.5%; banana, 0.23%; goldfish, 0.87%; palette heart, 0.77%; flat iron, 0.95%; Denver stake, 0.6%; beef steak, 0.40%; edible shavings, 19.43%; fat, 1.8%; scraps of disposal, 0.4%; discard bones, 17.9%. The proportion observed for the front and rear were 45.0 and 55.0%, respec- tively. There is a high volume of waste bones, which could be used in food, such as bone broth, for example. The volume of edible trimmings should be better used for making meat in cubes or as bait. The ground trimmings can be sold as ground meat or used in the preparation of hamburgers, sausages, meatballs, kafta, among others. Cuts that can be labeled premi- um make up approximately 25.0% of the carcass. Therefore, it is necessary to stimulate the daily consumption of buffalo meat in order to have a market for the other cuts that make up most of the carcass.